E‐Participation and Environmental Protection: Are Local Governments Really Committed?. (16th December 2013) - Royo, Sonia; Yetano, Ana; Acerete, Basilio
<x xml:space="preserve">Abstract</x> There is widespread acceptance that current institutions are inadequate to address the challenges of sustainable development. At the same time, there is an urgent need to build awareness and increase capacity for promoting action with respect to environmental protection at the local level. This article analyzes the Web sites of the environment departments of European local governments that signed the Aalborg Commitments to determine the extent to which they are using the Internet to promote e‐participation in environmental topics and to identify the drivers of these developments. Potential drivers are public administration style, urban vulnerability, external pressures, and local government environmental culture. Findings confirm that e‐participation is a multifaceted concept. External pressures influence the transparency of environmental Web sites, while public administration style and local government environmental culture influence their interactivity.